Cardiac troponin T for early detection of cardiotoxicity in breast cancer patients treated with epirubicin - DEDE, FUAT; TOKAY TARHAN, SENA (DE GRUYTER POLAND SP ZOO, 2009)
The aim of the study was to investigate the role of cTnT for the prediction of long term cardiac dysfunction after epirubicin-containing adjuvant chemotherapy for breast cancer. The study group comprised of 45 patients (all female; mean age 48 +/- 8 years), treated with epirubicin-containing adjuvant chemotherapy for stage 2 and stage 3 breast cancer. Patients received either 4 cycles of cyclophosphamide plus epirubicin (90 mg/m(2)) (n=23; stage 2 breast cancer) or 6 cycles of cyclophosphamide plus epirubicin (75 mg/m(2)) plus fluorouracil (n=18; stage 3 breast cancer). Venous blood samples were drawn, before and 72 hours after, every cycle of chemotherapy for the measurement of cTnT. Cardiac assessment was carried out at baseline and 1 year after chemotherapy by clinical evaluation, electrocardiography, radio-nuclide ventriculography (RNV) and transthoracic echocardiography. All patients remained free of clinical heart failure during the study period. In 26 patients (63%), cTnT was elevated after chemotherapy. Mean left ventricular ejection fraction, assessed by RNV at baseline and one year after chemotherapy, were 61 +/- 8% and 56 +/- 7% (p < 0.0001). The sensitivity and specifity of cTnT for the detection of left ventricular systolic dysfunction at one year were 69% and 39% respectively. Echocardiographic examinations at baseline and one year after chemotherapy revealed a significant decrease in E/A ratio from 1.15 +/- 0.3 to 0.9 +/- 0.2 in cTnT positive patients, suggesting diastolic dysfunction. In conclusion, elevated serum cTnT levels after epirubicin-containing adjuvant chemotherapy for stage 2 and stage 3 breast cancer, predict future cardiac dysfunction with moderate sensitivity and poor specificity.
Keywords: Breast cancer; Chemotherapy; Epirubicin; Cardiotoxicity; cTnT; ANTHRACYCLINE-INDUCED CARDIOTOXICITY; ADJUVANT CHEMOTHERAPY; DIASTOLIC FUNCTION; CHILDHOOD-CANCER; LEUKEMIA; SURVIVORS